1990
DOI: 10.1007/bf00224248
|View full text |Cite
|
Sign up to set email alerts
|

Abscisic acid deficiency prevents development of freezing tolerance in Arabidopsis thaliana (L.) Heynh.

Abstract: Abscisic acid (ABA) has been implicated as a regulatory factor in plant cold acclimation. In the present work, the cold-acclimation properties of an ABA-deficient mutant (aba) of Arabidopsis thaliana (L.) Heynh. were analyzed. The mutant had apparently lost its capability to cold acclimate: the freezing tolerance of the mutant was not increased by low temperature treatment but stayed at the level of the nonacclimated wild type. The mutational defect could be complemented by the addition of exogenous ABA to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
77
1
3

Year Published

1991
1991
2008
2008

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(91 citation statements)
references
References 24 publications
10
77
1
3
Order By: Relevance
“…These results indicated that levels of ABA in WT were not required for changes in gene expression that occurred during heat shock of detached tomato leaves. This is analogous to results obtained with an ABAdeficient mutant ofArabidopsis in response to cold stress (12). The same cold-induced polypeptides are observed in both genotypes.…”
Section: Hsp Synthesis Was Not Altered In the Aba-deficient Mutantsupporting
confidence: 87%
See 2 more Smart Citations
“…These results indicated that levels of ABA in WT were not required for changes in gene expression that occurred during heat shock of detached tomato leaves. This is analogous to results obtained with an ABAdeficient mutant ofArabidopsis in response to cold stress (12). The same cold-induced polypeptides are observed in both genotypes.…”
Section: Hsp Synthesis Was Not Altered In the Aba-deficient Mutantsupporting
confidence: 87%
“…This difference in heat tolerance may be a direct effect of ABA or an indirect effect. In response to low temperature stress, the ABA-deficient mutant of Arabidopsis is also slightly less tolerant and is not able to develop cold hardiness ( 12).…”
Section: Aba Levels In Response To Heat Shockmentioning
confidence: 99%
See 1 more Smart Citation
“…The frs1 mutation was found to be an allele of ABA3 (Llorente et al, 2000), confirming the necessity for normal abscisic acid signaling during cold acclimation (Heino et al, 1990). The freezing sensitivity of two sensitive to freezing (sfr) mutants has been interpretable in terms of prior knowledge about freezing tolerance.…”
Section: Introductionmentioning
confidence: 83%
“…This result is in agreement with the numerous lines of evidence supporting the critica1 role that ABA plays in plant adaptation to various forms of environmental water stress. For instance, the Arabidopsis aba mutant is impaired in cold acclimation (Heino et al, 1990;Gilmour and Thomashow, 1991). Mutations at the abil versus abi2 or abi3 loci clearly have a distinct effect on the intensity of drought rhizogenesis.…”
Section: Discussionmentioning
confidence: 99%